2013
DOI: 10.3892/br.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and uninephrectomy on renal changes in Tsukuba hypertensive mice

Abstract: Abstract. Renal dysfunction is accelerated by various factors such as hypertension, aging and diabetes. Glomerular hyperfiltration, considered one of the major risk factors leading to diabetic nephropathy, is often encountered in diabetic patients. However, the interrelationship of these risk factors during the course and development of renal dysfunction has not been fully elucidated. In this study, the effects of aging and uninephrectomy (UNx)-induced hyperfiltration on renal changes were investigated in Tsuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…CIRI refers to cellular function metabolic disorders and organizational structure damage aggravation following blood reperfusion of ischemic damage (11). Although timely blood reperfusion may rescue certain cells close to the site of infarction, reperfusion causes a greater extent of tissue damage than pure ischemia injury (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIRI refers to cellular function metabolic disorders and organizational structure damage aggravation following blood reperfusion of ischemic damage (11). Although timely blood reperfusion may rescue certain cells close to the site of infarction, reperfusion causes a greater extent of tissue damage than pure ischemia injury (11).…”
Section: Discussionmentioning
confidence: 99%
“…CIRI refers to cellular function metabolic disorders and organizational structure damage aggravation following blood reperfusion of ischemic damage (11). Although timely blood reperfusion may rescue certain cells close to the site of infarction, reperfusion causes a greater extent of tissue damage than pure ischemia injury (11). Previous studies have indicated that CIRI is primarily associated with inflammatory reactions, excitability amino acids, intracellular friction overload, oxygen free radicals and cell apoptosis (4,12).…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone affects not only the type1 angiotensin II receptor (AT1R) but also the angiotensin converting enzyme (ACE) and the renin receptor [4][5][6][7][8]. Hypertensive mice that systemically express human renin and human AGT show elevated renal angiotensin II levels [9]. We have reported that renal AGT gene expression is increased in salt-sensitive hypertensive rats and treatment with the AT1R blocker (ARB) or mineralocorticoid receptor antagonist (MRA) decreases the AGT mRNA levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte chemoattractant protein-1 (MCP-1) is weakly expressed in healthy humans. In nephridial tissues it is secreted by renal mesangial, renal tubular epithelial, vascular endothelial and mononuclear cells at damaged interstitial sites (6). MCP-1 expression levels are significantly increased in injured renal tubular epithelial cells (7).…”
Section: Introductionmentioning
confidence: 99%